2014
DOI: 10.2478/johr-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Texture Sensory Profiles and Optical Properties Measured by Time-Resolved Reflectance Spectroscopy During Post-Storage Shelf Life of ‘Braeburn’ Apples

Abstract: Abstract‘Braeburn’ apples from three harvests after 6-month storage in controlled atmosphere were measured at 670 nm by time-resolved reflectance spectroscopy (TRS), ranked on decreasing μa670 (increasing maturity), classified as less (LeM), medium and more mature (MoM), randomised into three batches per harvest and analysed after 1, 8 and 14 days of shelf life. LeM and MoM apples were measured in the 630-900 nm range by TRS, and analysed for sensory profile (firm, crispy, juicy, mealy) and pulp mechanical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…In our work, we found that µ′ sTRS , and µ′ sSRS to a lesser extent, were negatively related to mechanical and acoustic parameters, in agreement with Rizzolo et al (2010Rizzolo et al ( , 2014 and Vanoli et al (2010Vanoli et al ( , 2015Vanoli et al ( , 2018 for µ′ sTRS . During the shelf life period, 'Braeburn' apples softened as firmness significantly decreased.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In our work, we found that µ′ sTRS , and µ′ sSRS to a lesser extent, were negatively related to mechanical and acoustic parameters, in agreement with Rizzolo et al (2010Rizzolo et al ( , 2014 and Vanoli et al (2010Vanoli et al ( , 2015Vanoli et al ( , 2018 for µ′ sTRS . During the shelf life period, 'Braeburn' apples softened as firmness significantly decreased.…”
Section: Discussionsupporting
confidence: 81%
“…During the shelf life period, 'Braeburn' apples probably became mealy, as acoustic parameters also significantly decreased together with a dramatic increase of RISV: high values of mechanical and acoustic parameters accompanied with low RISV are characteristic of firm, crispy and juicy apples, while low values of mechanical and acoustic parameters with high RISV are typical of mealy apples, as found for 'Kanzi' and 'Braeburn' apples, respectively, by Vanoli et al (2018). Thus, the increase of µ′ sTRS observed in the present work could be due to the change of flesh texture from firm, crispy and juicy at harvest to mealy at the end of shelf life, as observed by Rizzolo et al (2014Rizzolo et al ( , 2019. In addition, Rizzolo et al (2010Rizzolo et al ( , 2014 and Vanoli et al (2010Vanoli et al ( , 2015Vanoli et al ( , 2018 found that µ′ sTRS was inversely related to sensory firmness, crispness and juiciness and positively related to mealiness and RISV.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The absorption coefficient m a may be related with components or chromophores of samples, and the reduced scattering coefficient m 0 s provides microstructure information [10]. Several methods for optical properties estimation have been reported, including time resolved method, frequency domain method and spatially resolved method [11,12]. However, both time resolved and frequency domain methods require expensive instruments which limits their applications.…”
Section: Introductionmentioning
confidence: 99%